(untitled) - FOS (Illinois, 1993)
This book builds step by step. Chapter 1 civers the principles of electricity - how it works. Chapter 2 explores the electron and how to measure it. Chapter 3-12 go into detail about the working parts of circuits. Chapter 13 and 14 then show how to properly maintain circuits as well as how to diagnose and test problem areas
Keywords: agricutural mechanics